STRATEGI KOMUNIKASI BRANDING DALAM UPAYA PENINGKATAN JUMLAH PESERTA DIDIK - Naning Yuliani; Imroatus Salsabila; Elok Fatkiyah; Asmaul Zakiatul Amalia; Khofifa Indi Lupidanti Sumarsosno; Devi Wahyu Mutiara Sari; Kharirotus Sa’adah (PANDU : Jurnal Pendidikan Anak dan Pendidikan Umum, 2025)
Competition among educational institutions is increasingly fierce, necessitating the creation of an attractive image to attract parents' interest in choosing a school for their children. One approach that can be implemented is communication.brandingThis research aims to describe the communication strategybrandingimplemented by MI Miftahul Ulum Kesamben Wetan to increase the number of new student registrations. This study used a qualitative approach with descriptive methods. Data collection was obtained through in-depth interviews with the principal, teachers, and parents, accompanied by observations of school activities and analysis of related documents. The data analysis process included data reduction, information presentation, and final conclusions. The research findings indicate that the communication strategybrandingcan be done internally or externally. This approach has been proven to contribute to the number of prospective students and increase the level of public trust in the school. Overall, this study concludes that communicationbrandingA holistic approach can be a powerful instrument for strengthening a school's reputation while increasing student enrollment.